Kaizen Approach to Quality Improvement and its Financial Implication (AFRICAN JOURNAL OF APPLIED RESEARCH, 2022)
Purpose: This study aims to investigate the impact of kaizen practice and how it affects the quality of large manufacturing firms particularly, Kilimanjaro international leather company.Design/methodology/approach. In this study, the Plan-Do-Check-Act (PDCA) cycle technique was employed to lower the production process's defect rate. The fishbone served as a tool for support. The PDCA cycle and fishbone are two top-notch techniques that aid in reducing the number of defective parts.Findings: The defect rate decreased by 2%. Improvement in the production process was achieved.Research limitation: One large manufacturing industry is insufficient to generalize the study's primary results. This will be achieved in the future by doing additional investigations in several large manufacturing firms.Practical implication: This study will provide consultants and practitioners with a valuable understanding of how Kaizen improves the financial performance of large manufacturing industries in Tanzania.Social Implications: The majority of learning exercises carried out during kaizen projects seek to enhance social outcomes in terms of staff members' problem-solving skills and attitudes. Particularly, Kaizen coordinators are concerned with group members' understanding of continuous improvement as well as their communication and problem-solving abilities.Originality/Value: Although some studies on kaizen have been conducted, it is currently discovered that there is insufficient literature on the application and impact of the kaizen concept in large manufacturing enterprises. Based on this case study, the framework of kaizen philosophy practices is offering useful insights for leather companies, other manufacturing industries, and organizations, including the Tanzania Kaizen unit, practitioners, and academicians.